The coast is clear redefining resilience in marginalized fisherfolk communities through an adaptive housing framework - Torres, Maria Gabriela Noelle C. (College of Architecture, University of the Philippines Diliman, 2022)
The question of the living conditions of vulnerable coastal communities amidst climate change and urbanization has been widely debated across fields including anthropology and DRRM. While DRRM and housing authorities suggest schemes for early warning signals, evacuation and relocation and resettlement, professionals in anthropology and other social science-based fields understand the mobile capacity of these vulnerable communities and their high threshold for resilience. This presents a gap in the knowledge of solutions to strengthen resilience in marginalized fisherfolk communities against climate change and urbanization that minimized the need for DRRM interventions and maximizes the potential of their homes. My paper addresses this gap with special attention to architectural design solutions. It seeks to answer the question: how can architectural design aid in strengthening overall resilience in marginalized fisherfolk community settlements in the context of climate change and urbanization? Specifically, I will be looking at possible solutions to the problem using related literature on vulnerable coastal communities and existing relevant architectural interventions that suggest methods for coastal revitalization and post-disaster reconstruction. These will then be studied against the current living conditions of the marginalized fisherfolk community of Isla Pugad, in order to propose a housing framework that can adapt to climate and livelihood conditions of similar communities. In this pursuit, I argue that architectural design is a more effective strategy for DRRM as opposed to current intangible solutions. This project, by closely examining the current living conditions and needs of vulnerable coastal communities and applying tangible DRRM architectural interventions, then sheds a new light on the neglected issue of vulnerable marginalized fisherfolk communities pressured by the effects of climate change and urbanization.